Enervări sau despre bucuria de a trăi în România - Bănică, Mirel 1971-; Constantinescu, Codruţ ca. 20./21. Jh (Ego : Publicistică, 2007)
Compilation of the messages sent on postcards between Bănică and Constantinescu over a period of 10 months. Each message contained some tidbit about the joys or in some instances, the irritations of living in Romania